ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL CERITA PENALARAN TINGKAT TINGGI (PTT) MATERI OPERASI HITUNG - Nurhudayana Ridwan; Rukli; Erwin Akib (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to analyze students' difficulties in solving PTT-based story problems with arithmetic operation material. This research uses a qualitative method with a descriptive approach. Data collection techniques in this study used tests, observation, and documentation. The subjects of this study were 30 students of class IV UPT SPF SD Inpres Mongisidi Makassar. The results obtained from the semantic differential scale related to the level of difficulty of the problem showed a decrease in percentage from the time of pre-research observation and during follow-up results, which was 60% to 20%. The results of the student questionnaire related to the ease of solving the problem also showed an increase from the time of pre-research observations and follow-up results, namely that there were only 15 students increasing to 22 out of 30 students. The cause of students having difficulty in working on story problems is because they do not understand the instructions, do not know how to solve the story problems, and do not understand the concept of arithmetic operations well because they are rarely given exercises using PTT problems so they are not used to reasoning and critical thinking.